Diagnóstico das práticas de planejamento, controle e acompanhamento da produção em canteiros de obras localizados na região metropolitana de Curitiba - Schaurich, Guilherme Felipe Schallenberger (2020)
The production planning, control and monitoring play a fundamental role in the performance of civil construction. Even só, companies in the sector focus their actions on the enterprise as a whole, without paying due attention to production itself. In view of this, this study sought to make a diagnosis of the practices of planning, control and monitoring of production within construction sites in the Metropolitan Region of Curitiba. Initially, a bibliometric analysis was developed on the subject, with the objective of identifying relevant studies in this area that could then be used as a theoretical foundation and, later, to compare the results found in this research. After carrying out the bibliometric analysis and the theoretical foundation, an applied, descriptive and quantitative research was carried out in order to better understand how the management of construction processes is carried out in practice. Using a structured questionnaire with a semantic differential scale, data were collected from professionals working on construction sites. From the data collected, technical analyzes of descriptive statistics and correlation were performed. The results were then expressed in the form of tables with statistical descriptors, histograms, boxplot charts and spreadsheets with Spearman’s correlation coefficients. It was then possible to observe the panorama of production management practices within construction sites, with both planning and control and monitoring of production showing similar results of development in the companies evaluated. As for the correlation of these practices with the others, it was clear that the control and monitoring has a greater association with the other factors present in the production management, while the planning is carried out in a more isolated way from the other characteristics of the civil construction production.